An experimental study on the effectivity of backschool in reducing the occurrence of low back pain in UPCD clinicians SY 2000-2001 - Concepcion, Jerick P.
A Back School is a lecture on the maintenance and prevention of back pain through the integration of proper ergonomics, exercises and posture. It is thus essential to know and practice these instructions in an individual's daily activities to treat or prevent him/her from developing Low Back pain. The aim of the study was to determine the effectivity of back school in reducing the incidence of Low Back pain in University of the Philippines College of Dentistry senior (40) clinicians, SY 2000-2001. Thirty-nine senior clinicians participated in the study. Data was gathered using a survey questionnaire and the pain scale drawing or visual analog scale (VAS) and was assessed using descriptive statistics and the t-test. Results showed that 71.79% of the population experience mechanical/postural low back pain while only 20.51% never had low back pain and 7.2% were found to have skeletal or systemic low back pain. The respondents with mechanical low back pain were distributed into an experimental and control group. In the experimental group, 15 out 16 subjects experienced a significant reduction of pain. In the control group, all subjects had a "rise and fall" trend in pain at a smaller standard deviation per individual. When the means of both groups were compared, the pain reduction is evident on the experimental group. The findings of the study support the statement of De Orazio that mechanical/postural LBP can be reduced by back strengthening ang stretching exercise, along with the knowledge and application of proper posture and correct ergonomic practices. However, factors such as mental stress, muscle fatigue and the presence of poor working conditions were not considered in the study, which might have been unseen factors on the subjects, pain perception.